The Influence of Internal Environmental Factors in Coffee Farming on Farmer Participation in Farming Groups in Sub-district of Ronggur Nihuta, Samosir District - Rabbani, Ali; Lindawati, Lindawati; Wibowo, Rulianda P. (JURNAL AGRICA, 2025)
This research will focus on PTPN IV Regional II with the aim of exploring priority strategies that can be applied to obtain RSPO certification. With a systematic approach, this study is expected to provide practical benefits for the company and contribute to the literature in the field of agribusiness sustainability strategy. Data collection uses primary data and secondary data with a SWOT analysis approach and QSPM analysis. Increasing the number of RSPO-certified units in 1-2 years. Reducing certification costs by 15% through collaboration or clustering. Increase in demand for certified products in the global market by at least 10% per year. SWOT analysis to make a plan must evaluate external and internal factors. The QSPM analysis stage is Determining EFEM, at this stage external factors are determined and evaluated. Determining IFEM, at this stage internal factors are determined and evaluated. The results of the study indicate that the partnership strategy with certification bodies and the utilization of technological advances are the main priorities to support the success of PTPN IV in obtaining RSPO certification. This strategy plays an important role in strengthening the company's position in the global market while achieving sustainability goals. With a structured and measurable approach, PTPN IV can not only obtain RSPO certification, but also improve its reputation as a leader in the sustainable palm oil industry. Strengthening internal capacity through HR training and cost efficiency are key factors in facing the challenges of certification costs and regulatory pressures. In addition, market diversification helps companies mitigate the risk of dependence on certain markets, such as Europe.